Pemasaran Islami dan minat pelanggan: Menjembatani teori dan praktik dari perspektif ekonomi Islam - Try Astuti, An Ras; Faisal, Andi (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2023)
Competition between Banks continues to develop. Banking management requires a competitive strategy in increasing the number of customers. it is then interesting to investigate how the limits of Islamic marketing strategies in increasing interest in becoming customers in Banking.This writing uses qualitative research by looking at phenomena that occur through observation. The data collected is relevant to the needs that focus on identifying Islamic marketing strategies that are in context with current needs. The data obtained is then classified, arranged and listed. The validity of the data uses a credibility test with source triangulation with data analysis which is used as a reference using stages and linkages which include data reduction, data presentation, and drawing conclusions or verification.The results of this study indicate the efforts of BTN Syariah Parepare in increasing customer interest by introducing products through socialization and promotion by BTN Syariah employees using brochures or face-to-face BTN Syariah Parepare in marketing applying sharia principles, namely employees believe that Allah Swt will always be there in every activity so that it is implemented in a fair and honest manner in marketing, employees are friendly and polite in serving customers, employees have an adaptive and proactive attitude and absorb the human side in marketing their products. All of these principles are framed in a work culture, abbreviated as AKHLAK. Thus we support the view that the relationship between Islamic Banking and risk depends on the regulatory framework that applies in the Banking work culture.